Strategy for improving human resource quality in government administration in Indonesia, Sytematic Literature Review - Fitri, Fitri; Laduppa, Hardianti; Sellang, Kamaruddin; Budai, Balázs Benjámin (ARISTO, 2026)
This study aims to map the development of research and scientific publications related to strategies to improve the quality of human resources in Indonesian government administration. This research uses the Sytematic Literature Review (SLR) approach by following the PRISMA protocol and analyzing 64 relevant scientific articles from the Dimension database, published in 2013-2024. The analysis was conducted using VOSviewer to identify topic clusters, related concepts. As well as research trends. The results revealed that there are five main clusters that are dominant and relevant in the development of human resources for government officials, namely: education, HR management, technology, digital literacy, bureaucratic reform, and public service innovation. The education cluster emerged as the most dominant theme, showing the importance of literacy and continuous training in supporting the digital transformation of the bureaucracy. This research makes a significant contribution to the development of ASN capacity building policies through a data-based approach and scientific trends. In addition, these findings also serve as a strategic reference in strengthening HR management systems and technology-based governance. The limitation of this study lies in the data source that only comes from the data dimension, so that the coverage of the literature does not represent the whole of various relevant sources. Therefore, future studies are advised to combine data from various reputable databases such as Scopus, Web of Science, and EBSCO for more comprehensive results.